Polynomial approximations of solutions of higher-order operator-differential equations - Orudzhev, G. D. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the Cauchy problem for higher-order operator-differential equations in a Banach space and construct polynomial approximations of its solutions.